Optical Recording of Action Potentials in Human Induced Pluripotent Stem Cell-Derived Cardiac Single Cells and Monolayers Generated from Long QT Syndrome Type 1 Patients. (6th March 2019) - Takaki, Tadashi; Inagaki, Azusa; Chonabayashi, Kazuhisa; Inoue, Keiji; Miki, Kenji; Ohno, Seiko; Makiyama, Takeru; Horie, Minoru; Yoshida, Yoshinori
Abstract : Induced pluripotent stem cells (iPSCs) from type 1 long QT (LQT1) patients can differentiate into cardiomyocytes (CMs) including ventricular cells to recapitulate the disease phenotype. Although optical recordings using membrane potential dyes to monitor action potentials (APs) were reported, no study has investigated the disease phenotypes of cardiac channelopathy in association with the cardiac subtype at the single-cell level. We induced iPSC-CMs from three control and three LQT1 patients. Single-cell analysis using a fast-responding dye confirmed that ventricular cells were the dominant subtype (control-iPSC-CMs: 98%, 88%, 91%; LQT1-iPSC-CMs: 95%, 79%, 92%). In addition, LQT1-iPSC-ventricular cells displayed an increased frequency of early afterdepolarizations (p value = 0.031 ). Cardiomyocyte monolayers constituted mostly of ventricular cells derived from LQT1-iPSCs showed prolonged AP duration (APD) (p value = 0.000096 ). High-throughput assays using cardiomyocyte monolayers in 96-well plates demonstrated that IKr inhibitors prolonged APDs in both control- and LQT1-iPSC-CM monolayers. We confirmed that the optical recordings of APs in single cells and monolayers derived from control- and LQT1-iPSC-CMs can be used to assess arrhythmogenicity, supporting the feasibility of membrane potential dye-based high-throughput screening to study ventricular arrhythmias caused by genetic channelopathy or cardiotoxic drugs.